2016
DOI: 10.1177/1558944715617222
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes Following Surgically Managed Perilunate Dislocation

Abstract: Surgical treatment of PLDs can provide good clinical outcomes allowing patients to return to normal activities in a reasonable timescale when delays to surgery are kept to a minimum. The PRWE demonstrated high internal consistency and was found to be a valid questionnaire with advantages over the DASH for use following severe carpal injures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…(2) The dorsal approach offers adequate exposure of the proximal carpal row and the mid-carpal joint [4][5][6]. The space produced by the luxation allows easy Kirschner wire placement in both the scaphoid for scapho-lunate transfixation and the triquetrum for triquetro-lunate fixation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2) The dorsal approach offers adequate exposure of the proximal carpal row and the mid-carpal joint [4][5][6]. The space produced by the luxation allows easy Kirschner wire placement in both the scaphoid for scapho-lunate transfixation and the triquetrum for triquetro-lunate fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have suggested a dorsal approach as it offers the benefit of adequate exposure of the proximal carpal row and mid-carpal joint [4][5][6][7][8]. A complementary volar approach [9] allows access to distal scaphoid fractures and repair of the volar ligaments and capsular rent as well as the release of the carpal tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…In the current case, the reduction was anatomic and it was achieved noticeably short after the operation. Furthermore, authors could be relied upon to be in contact with the patient in case of any loss of reduction (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of this complex injury may be missed in up to 25% of the patients, and up to 50% of patients may present with acute carpal tunnel symptoms [5][6][7]. Early diagnosis and treatment is essential to avoid long term disability, as delayed treatment is associated with poor outcomes [5,8,9].…”
Section: Introductionmentioning
confidence: 99%